Fostering Consumer–Brand Relationships through social media brand communities - Santos, Zélia Raposo (2022)
Santos, Z. R., Coelho, P. S., & Rita, P. (2022). Fostering Consumer–Brand Relationships through social media brand communities. Journal of Marketing Communications, 28(7), 768-798. https://doi.org/10.1080/13527266.2021.1950199 ---%ABS1%